Analysis of Existential Feminism Struggle of Women Online Drivers During the Covid-19 Pandemic - Allen Pranata Putra; Erwan Aristyanto (HUMANISMA : Journal of Gender Studies, 2021)
This article discusses the women's movement to sustain its existentialism in the COVID-19 pandemic by moving and taking high risks to become female online drivers. Based on research conducted by Simone De Beauvoir, who analyzed the film "The Second Sex" using existentialist feminism theory, women are often used as objects and men as subjects because of the man's masculinity and biological circumstances that are considered to support inter-subjective in men. The contribution of this research is the use of existentialist feminism as an anti-thesis of male masculinity by applying it to the empirical conditions of women. The study used feminist ethnographic methods that combine ethnographic interviews and participant observations. The focus of this study lies on the class struggle of women to maintain their existentialism despite having to take high job risks and the risk of contracting the COVID-19 virus due to high mobility. This research data analysis technique uses data reduction, data display, and data triangulation. The results showed that women worked as online drivers to become subjects for themselves and act as breadwinners and housewives in the conditions of the COVID-19 pandemic. Women's struggles in the COVID-19 pandemic undermine the social stigma of society that often makes them objects.Artikel ini membahas tentang gerakan kaum perempuan untuk mempertahankan eksistensialnya di masa pandemi COVID-19 dengan bergerak dan mengambil resiko tinggi untuk menjadi driver online perempuan. Berdasarkan penelitian yang dilakukan oleh Simone De Beauvoir yang menganalisis film “The Second Sex”menggunakan teori feminisme eksistensialis, perempuan seringkali dijadikan sebagai objek dan laki-laki sebagai subjek karena maskunilitas dari seorang laki-laki dan keadaan biologis yang dianggap mendukung adanya inter-sebujektif pada laki-laki. Kontribusi penelitian ini adalah penggunakan feminisme eksistensialis sebagai anti-thesis maskulinitas laki-laki dengan menerapkan pada kondisi empiris perempuan. Penelitian ini menggunakan metode etnografi feminis yaitu menggabungkan ethnographic interview dan participant observations. Fokus penelitian ini terletak pada class struggle kaum perempuan untuk mempertahankan eksistensialnya meskipun harus mengambil resiko pekerjaan yang tinggi dan resiko tertular virus COVID-19 akibat mobilitas yang tinggi. Teknik analisis data penelitian ini menggunakan reduksi data, display data, verifikasi data dan triangulasi data. Hasil menunjukkan bahwa kaum perempuan bekerja sebagai driver online untuk menjadi subjek bagi dirinya sendiri sekaligus berperan sebagai pencari nafkah dan ibu rumah tangga dalam kondisi pandemi COVID-19. Perjuangan perempuan dalam pandemi COVID-19 meruntuhkan stigma sosial masyarakat yang seringkali menjadikan mereka sebagai objek.